Interpreting the Fukushima Daiichi nuclear incident: some questions for corporate criminology - Levi, Michael (Crime, law and social change, 2013)
The serious nuclear incident at Fukushima Daiichi, triggered by the tsunami following the Tohuku earthquake on 11th March 2011, has prompted a flurry of investigations and debates of various kinds, within Japan and beyond. In common with many other such disasters, the causation of which brings together technologies, human behavior, organizational and regulatory cultures, and physical settings in complex configurations, serious questions have been asked about whether corporate crime was involved in creating this nuclear disaster. Of course the failure was prompted by an enormously powerful natural phenomenon, but should the operating company and government bodies have been better prepared? If so, who was to blame? Do attempts to explain the disaster in terms of cultural categories amount to a ‘cop out’; serving to excuse responsible individuals for acts both of commission and omission? In this paper, we examine these questions, focusing on the inherent ambiguity of such untoward events, and the difficult political and legal conundrums to which they can lead.